Antara Ali Yafie dan KH. Sahal Mahfudz: Perbandingan Pemikiran Fiqh Sosial dan Relevansinya dengan Indonesia Modern - Syihabuddin, Muhammad; Fauzie, Nadya Amri; Khasri, Muhammad Ilham Ulul Azmi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2024)
This research compares the thinking of KH. Ali Yafie and KH. Sahal Mahfudz in the concept of social fiqh and its relevance to modern challenges in Indonesia. These two figures have a unique approach to formulating social fiqh: KH. Ali Yafie emphasized the harmony between traditional Islamic principles and the modern context, focusing on social, economic, and environmental justice, while KH. Sahal Mahfudz carries the method of "fiqh lil maqasid," which is pragmatic and places the community's welfare as the main goal. This research method uses qualitative methods with a case study approach. Primary sources are in the form of KH's work. Ali Yafie, Initiating Social Jurisprudence, and KH. Sahal Mahfudz, Nuances of Social Fiqh, combined with supporting articles. The data were analyzed through the examination, classification, and interpretation stages, resulting in conclusions relevant to Indonesia's modernization context. The results showed that these two ideas complement each other in presenting solutions to social issues, such as poverty alleviation, inclusive policies, and environmental conservation. KH. Ali Yafie emphasized the importance of Islamic ethics in public policy, while KH. Sahal Mahfudz highlighted community participation in decision-making. In the modern era and technological disruption, both recommend the use of digital technology for social education and community empowerment to reduce economic disparities. The social fiqh they found is relevant to creating sustainable social justice and supports the vision of Islam as rahmatan lil ‘alamin. This approach also confirms the importance of synergies between scholars, intellectuals, government, and society to produce adaptive solutions to modern challenges.